Design and Development of Course and Education Scheduling Using Genetic Algorithm - Sukma Mahardhika, I Made Surya; Adriani, Ni Luh; Oka Saputra, Komang (International Journal of Engineering and Emerging Technology, 2019)
This study discusses the problems that occur in Warmadewa College Training and Course Institutions. The problems that occur are the presence of instructors who mostly work as lecturers resulting in the difficulty of determining and scheduling courses and training in accordance with the time of each instructor. Another problem is the process of making a course schedule and training that is still done manually resulting in difficulties in processing student data and schedules. This system is designed to facilitate academic, instructor and student access to information on course scheduling and training. The method used to solve these problems is by using Genetic Algorithms and using the PIECES method to analyze problems and use the Rapid Application Development (RAD) method as a system development model. The results of this study provide convenience in managing the process of scheduling courses and training efficiently and effectively in accordance with the instructor's time and available space so that the process of making the schedule can run well.